Production of Powders by the Method of Electrospark Dispersion; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Zhuravkov S. P. Sergey Petrovich; Kornev Ya. I. Yakov Ivanovich; Ivashutenko A. S. Alexander Sergeevich; Martyushev N. V. Nikita Vladimirovich (Discharge and Plasma-Beam Technology, 2016)
Title screen